From the Mountain Tops to the Middle of the Ocean: Scholars Calling for Collaboration (Comparative & International Education Series, 2022)
This book, Humane World through Global Higher Education: Pre-Challenges and Post-Opportunities During a Pandemic, is a collaborative written endeavor prompted by the 2020 STAR Global Conference. Nepal Open University hosted the Conference around the theme Shaping a Humane World. 2020 was a heady moment of pride and panic against a backdrop of politics and pandemics undergirded by a wave of nationalism and racial awakening. How to cite in APAGaulee, U. (2022). From the mountain tops to the middle of the ocean: Scholars calling for collaboration. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 163-168). STAR Scholars.